ANALYSIS OF INTERNAL CONTROL SYSTEM IN COLLECTION OF TRANSPORT TERMINAL RETRIBUTIONS AS REGIONAL ORIGINAL INCOME NORTH TAPANULI DISTRICT (Case Study at North Tapanuli Transportation Service - Mutiara hutabarat; Melinda malau; Desideria Regina (Universitas Kristen Indonesia, 2023)
This study aims to determine the effectiveness of internal control in collecting transportation terminal retribution as a source of local revenue (PAD) in Taput Regency. This research is descriptive analysis. The population in this study were all employees of the Dishub Office of North Tapanuli Regency, while the sample in this study was 40 employees who had an interest in the activities of collecting levies from the terminal to depositing the results of the levy to the bank. The hypothesis in this study is suspected that the internal control system in collecting retribution for transportation terminals in North Tapanuli district as a source of local revenue has been implemented effectively. Data collection was carried out using a questionnaire technique and supported by interview techniques with related parties. Keywords: System Analysis, Internal Control System.